Keragaman Genetik Plasma Nutfah Pisang (Musa Spp.) Berdasarkan Karakter Morfologi di Provinsi Jambi - Maulana, Muhammad; Sarman S, Sarman S; Wiskandar, Wiskandar; Nusifera, Sosiawan; Riduan, Ahmad - (Jurnal Media Pertanian, 2024)
This study aims to gather data on the genetic diversity of banana germplasm through morphological characteristics in Jambi Province. It also seeks to characterize each banana type present in the region and assess the diversity and relationships among banana plants to establish distinct groupings based on their traits. The findings indicate that quantitatively, there are four relative criteria ranging from very narrow to very broad, reflecting diversity. Qualitatively, there is observed diversity across characteristic criteria spanning from very narrow to very broad. Morphologically, bananas in Jambi Province are classified into eight groups, each distinguished by unique identifying characteristics. Correlation analysis reveals that the relationship between morphological diversity and soil pH, soil moisture, and altitude in Jambi Province is notably weak and non-significant.